IFN-γ enhances the antitumor activity of attenuated salmonella-mediated cancer immunotherapy by increasing M1 macrophage and CD4 and CD8 T cell counts and decreasing neutrophil counts - Xu, Huimin; Piao, Linghua; Wu, Yundi; Liu, Xiande (Frontiers in Bioengineering and Biotechnology, 2022)
Bacteria-mediated cancer immunotherapy (BCI) inhibits tumor progression and has a synergistic antitumor effect when combined with chemotherapy. The anti- or protumorigenic effects of interferon-γ (IFN-γ) are controversial; hence, we were interested in the antitumor effects of IFN-γ/BCI combination therapy. Here, we demonstrated that IFN-γ increased the tumor cell killing efficacy of attenuated Salmonella by prolonging the survival of tumor-colonizing bacteria via blockade of tumor-infiltrating neutrophil recruitment. In addition, IFN-γ attenuated Salmonella-stimulated immune responses by stimulating tumor infiltration by M1-like macrophages and CD4+ and CD8+ T cells, thereby facilitating tumor eradication. Taken together, these findings suggest that combination treatment with IFN-γ boosts the therapeutic response of BCI with S.tΔppGpp, suggesting that IFN-γ/BCI is a promising approach to immunotherapy.